(untitled) (Wire Insights: Journal of Innovation Insights, 2026)
This article examines the role of critical reading and critical thinking in the development of academic writing and effective learning processes. It emphasizes that students should not passively accept information presented in academic texts but should analyze, question, and evaluate it through comparison with other sources and by assessing the validity of research methods and arguments. The study highlights the close relationship between critical reading and critical thinking, explaining that critical reading enables readers to understand the explicit and implicit meanings of a text, while critical thinking allows them to evaluate ideas, make judgments, and form independent conclusions. The article also reviews theoretical perspectives from various scholars on the definitions and importance of critical thinking and reading. In addition, it discusses pedagogical approaches and instructional models that can help educators develop these skills among learners at different educational stages. The findings suggest that critical reading and higher-order thinking skills should be systematically taught from early education through higher education to prepare students for independent learning, academic success, and responsible participation in society